Is the VO2 slow component dependent on progressive recruitment of fast-twitch fibers in trained runners? - Borrani, F.; Candau, R.; Millet, G. Y.; Perrey, S.; Fuchslocher, J.; Rouillon, J. D. (Journal of Applied Physiology, 2001)
The goal of this study was to use spectral analysis of EMG data to test the hypothesis that the O2 uptake (VO2) slow component is due to a recruitment of fast fibers. Thirteen runners carried out a treadmill test with a constant speed, corresponding to 95% of the velocity associated with maximal VO2. The VO2 response was fit with the classical model including three exponential functions. Electrical activity of six lower limb muscles (vastus lateralis, soleus, and gastrocnemius of both sides) was measured using electromyogram surface electrodes. Mean power frequency (MPF) was used to study the kinetics of the electromyogram discharge frequency. Three main results were observed: 1) a common pattern of the MPF kinetics in the six muscles studied was noted; 2) MPF decreased in the first part of the exercise, followed by an increase for all the muscles studied, but only the vastus lateralis, and gastrocnemius muscles of both sides increased significantly (P < 0.05); and 3) the beginning of the MPF increase of the four muscles mentioned above corresponded with the beginning of the slow component. Our results suggest a progression in the average frequency of the motor unit discharge toward the high frequencies, which coheres with the hypothesis of the progressive recruitment of fast-twitch fibers during the VO2 slow component. However, this interpretation must be taken with caution because MPF is the result of a balance between several phenomena.